Enhanced Room‐Temperature Photoluminescence Quantum Yield in Morphology Controlled J‐Aggregates. Issue 4 (4th January 2021) - Anantharaman, Surendra B.; Kohlbrecher, Joachim; Rainò, Gabriele; Yakunin, Sergii; Stöferle, Thilo; Patel, Jay; Kovalenko, Maksym; Mahrt, Rainer F.; Nüesch, Frank A.; Heier, Jakob
Abstract: Supramolecular assemblies from organic dyes forming J‐aggregates are known to exhibit narrowband photoluminescence with full‐width at half maximum of ≈9 nm (260 cm −1 ). Applications of these high color purity emitters, however, are hampered by the rather low photoluminescence quantum yields reported for cyanine J‐aggregates, even when formed in solution. Here, it is demonstrated that cyanine J‐aggregates can reach an order of magnitude higher photoluminescence quantum yield (increase from 5% to 60%) in blend solutions of water and alkylamines at room temperature. By means of time‐resolved photoluminescence studies, an increase in the exciton lifetime as a result of the suppression of non‐radiative processes is shown. Small‐angle neutron scattering studies suggest a necessary condition for the formation of such highly emissive J‐aggregates: the presence of a sharp water/amine interface for J‐aggregate assembly and the coexistence of nanoscale‐sized water and amine domains to restrict the J‐aggregate size and solubilize monomers, respectively. Abstract : The narrowband photoluminescence quantum yield at room temperature of supramolecular assemblies of cyanine dyes (J‐aggregates) is enhanced from 5% to 60%. Confinement of J‐aggregates in a bicontinuous phase in water–alkylamine blends improves the quality of the J‐aggregates.